Primary Screwworm Cochliomyia hominivorax (Coquerel) (Insecta: Diptera: Calliphoridae) - Phillip E. Kaufman; Samantha M. Wisely; Jennifer L. Gillett-Kaufman (EDIS)
In October of 2016, the United States Department of Agriculture confirmed that the primary screwworm, also called the New World screwworm, has returned to Florida. The fly was found infesting Key deer on Big Pine Key. Key deer are an endangered species found only on the Florida Keys, and unfortunately several have died from the 2016 screwworm infestations, but the screwworm is not only a problem for deer and other wildlife. The pest poses a serious threat to all warm-blooded animals, including livestock, pets, and people, and it cost the US livestock industry billions of dollars before it was finally eradicated decades ago. This 5-page fact sheet provides more information about this dangerous pest and how to spot it, as well as what to do and whom to contact if you suspect an infestation in your livestock, pets, or in a wild animal. Written by Phillip E. Kaufman, Samantha M. Wisely, and Jennifer L. Gillett-Kaufman, and published by the Entomology and Nematology Department, October 2016.